2007
DOI: 10.3748/wjg.13.6269
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between vascular invasion and microvessel density and micrometastasis

Abstract: AIM:To evaluate the relationship between vascular invasion and microvessel density (MVD) of tissue and micrometastasis in blood. M E T H O D S :V a s c u l a r i n v a s i o n w a s d e t e c t e d b y b o t h h e m a t o x y l i n a n d e o s i n s t a i n i n g a n d immunohistochemiscal staining. Blood samples were collected from 17 patients with vascular invasion and 29 patients without vascular invasion and examined for cytokeratin20 (CK20) expression by reverse transcriptase-polymerase chain reaction (RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
1
7
0
2
Order By: Relevance
“…It has been discovered that MVD is closely related to tumor invasive ability, metastasis and prognosis (Yan et al 2008). As a reliable index for quantifying the degree of angiopoiesis, MVD is considered to predict the tumor metastasis in many human tumors (Wang et al 2007a). CD31, a relatively speciWc marker for tumor vascular endothelial, was used to stain microvessels in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been discovered that MVD is closely related to tumor invasive ability, metastasis and prognosis (Yan et al 2008). As a reliable index for quantifying the degree of angiopoiesis, MVD is considered to predict the tumor metastasis in many human tumors (Wang et al 2007a). CD31, a relatively speciWc marker for tumor vascular endothelial, was used to stain microvessels in our study.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study has established that the density of microvessels is almost doubled in tumors from patients with metastasis [46]. While the presence of vascular invasion is not a consistent finding, it is still linked to increased incidence of lymph node, distant metastasis, and a corresponding decrease in survival [47]. …”
Section: Discussionmentioning
confidence: 99%
“…In the majority of reports, increase in tumour vascularisation favours the growth and remote dissemination of the cancer cells and is, therefore, a predictor of poor outcome in CRC [1628]. On the other hand, some authors have reported higher survival rates in tumours with high MVD.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, similar studies have been performed on colorectal cancer (CRC). The results of those studies are controversial because although the majority of them reported an association between a greater microvascular density, remote metastasis, and patient survival [1628], others did not [2931], and in some cases, high MVD was associated with better prognosis [3235]. …”
Section: Introductionmentioning
confidence: 99%